Equation of Tangent line
is the negative reciprocal to the slope of the tangent line. x2 + y2 = 100 circle 4x – 3y = 50 tangent line (8,6) point of tangency The slope of the radius is the negative reciprocal to the slope of the tangent line. mr = mt = The circle above is defined by the equation: x2 + y2 = 100. A tangent line (4x – 3y = 50) intersects the circle at a point of tangency: (8,6). The tangent line is perpendicular to the radius of the circle. The circle above is defined by the equation: x2 + y2 = 100. A tangent line (4x – 3y = 50) intersects the circle at a point of tangency: (8,6). The tangent line is perpendicular to the radius of the circle. The circle above is defined by the equation: x2 + y2 = 100. A tangent line (4x – 3y = 50) intersects the circle at a point of tangency: (8,6). The tangent line is perpendicular to the radius of the circle. The circle above is defined by the equation: x2 + y2 = 100. A tangent line (4x – 3y = 50) intersects the circle at a point of tangency: (8,6). The tangent line is perpendicular to the radius of the circle.
When a tangent and a radius intersect at the point of tangency, they are always perpendicular to each other. It then follows that their slopes are always negative reciprocals of each other. T(0,-3) P(2,-1) C(-1,2) P(2,-1) mr =
Find the slope of the line tangent to the circle x2 + y2 = 5 and passing through the point R(-2,1).
Find the equation of the tangent to the circle x2 + y2 + 10x – 24y = 0 and passing through the point T(0,0). Step 1: Find the centre and the radius. x2 + y2 + 10x – 24y = 0 (x2 + 10x + 25) + (y2 – 24y + 144) = 0 + 25 + 144 (x + 5)2 + (y – 12)2 = 169 Step 3: Find the slope of the tangent. Centre: (-5,12) r = 13 Step 2: Find the slope of the radius. Step 4: Find the equation of the tangent. 12(y – 0) = 5(x – 0) 12y = 5x 5x – 12y = 0
Find the equation of the tangent to the circle x2 + y2 – 6y - 16 = 0 and passing through the point T(3,7). Step 1: Find the centre and the radius. x2 + y2 – 6y - 16 = 0 x2 + (y2 – 6y + 9) = 16 + 9 x2 + (y – 3)2 = 25 Centre: (0,3) r = 5 4(y – 7) = -3(x – 3) 4y - 28 = -3x + 9 3x + 4y = 9 + 28 3x + 4y = 37
finito